Clinical and Radiological Comparisons of Percutaneous Low-Power Laser Discectomy and Low-Temperature Plasma Radiofrequency Ablation for Cervical Radiculopathy: A Prospective, Multicenter, Cohort Study - Lan, Xueqin; Wang, Ziyang; Huang, Yuzhao; Ni, Yuncheng; He, Yunwu; Wang, Xiaofeng; Wu, Chunsheng; Hu, Rong; Han, Rui; Guo, Gangwen; Li, Zhenxing; Zhang, Xuan; et al. (Frontiers in Surgery, 2022)
Background: Minimally invasive techniques such as percutaneous low-power laser discectomy (PLLD) and low-temperature plasma radiofrequency ablation (coblation) can be applied to treat degenerative cervical radiculopathy. However, less evidence supports the superiority of distinct minimally invasive therapy. Our study aimed to evaluate the clinical and radiological characteristics of the PLLD and coblation for cervical radiculopathy. Methods: This was a prospective, multicentre, cohort study (ChiCTR-ONC-17010356). The modified Macnab criteria was performed to assess the clinical improvement pre- and post-surgery. To evaluate the radiological effect, the Pfirrmann grading system and disc herniation index were applied with magnetic resonance imaging. Results: In this study, twenty-eight patients were enrolled in the coblation group and 30 patients in the PLLD group. The mean good-excellent rate at 3-month follow-up was 82.1% for PLLD group, and 66.7% for coblation group, respectively (P=0.179). The PLLD group achieved higher good-excellent rate 6 and 12 months after discharge (92.9% versus. 70.0%, P=0.026). Radiological data revealed that PLLD but not coblation treatment achieved significant reduction of disk herniation index (P<0.0001). Coblation treatment did change the Pfirrmann grades of cervical radiculopathy patients (n=18), and 7 out of 17 (41.2%) patients achieved improvement after PLLD therapy. None obvious adverse event was observed in this study. Conclusion: Both PLLD and coblation are effective and safe option for patients with cervical radiculopathy. Better long-term clinical outcomes may be potentially associated with improvement of disc degeneration after PLLD treatment.